The industrial organization of input markets - Prasad, K (2012)
This thesis consists of three closely connected pieces of work and an enhanced version of my M.Phil. thesis. The first three substantive chapters analyse vertical contracting in input markets under the exercise of differential buyer power. Chapters 2 and 3 consider the case of a supplier selling its output via a supermarket that offers captive demand (due to customers who anyway make a trip for their weekly shopping), which its rival, a local store is not able to offer. It is shown that the supermarket can negotiate an input price lower than the local store's only if its advantage translates into sufficient bargaining strength in setting contracts. The existence of a waterbed effect, the implications of a partially covered market, a nonlinear pricing structure and welfare implications of a ban in discrimination are also explored. Chapter 4 modifies the standard model where size determines buyer power to show that if quantities need to be decided in advance, an increase in a retailer's size is always welfare improving. For the presence of waterbed effects, we propose a novel insight that runs across different classes of models: following a discount to one retailer, the supplier faces two competing incentives - it wants to extract profits from the rival retailer but it also wants to transfer sales towards it. The waterbed effect is shown to be present only if the discount to the retailer is small, so incentives for profit extraction outweigh those for transferring business. Finally chapter 5 studies a firm's strategic incentive to outsource when its product displays network effects. It shows that a firm would choose to increase its observable marginal cost to make its competitor less aggressive and thereby increase its own probability of winning competition for the market. This is robust to small levels of uncertainty.